GANGGUAN BERBAHASA PADA ANAK PENDERITA ATTENTION DEFICIT DISORDER (GANGGUAN PEMUSATAN PERHATIAN) STUDI KASUS KEPADA ICHSAN MUHAMMAD AKBAR - Murnianti Murnianti; Gusdi Sastra; Rina Marnita (JURNAL ARBITRER, 2015)
Jurnal Arbitrer CULTURAL ELEMENTS FOUNDIN LAURA INGALLS WILDER’SLITTLE HOUSE IN THE BIG WOODSFOR SUPPORTING ENGLISH TEACHING Giyatmi, Ratih Wijayava, Nunun Tri WidarwatiProgram Studi Pendidikan Bahasa Inggris, FKIPUniversitas Veteran Bangun Nusantara Abstract Vol 2 No 3, September 2015 GANGGUAN BERBAHASA PADA ANAK PENDERITAATTENTION DEFICIT DISORDER/ADD(GANGGUAN PEMUSATAN PERHATIAN)STUDI KASUS KEPADA ICHSAN MUHAMMAD AKBAR Murnianti, Gusdi Sastra, Rina MarnitaGusdi Sastra, Rina MarnitaProgram Studi LinguistikPascasarjana Fakultas Ilmu Budaya Universitas Andalas Abstract This thesis is aimed at identifying and explaining the form of receptive disorder, describing the form ekspresive (productive) disorder, and investigating nonlinguistics factors which cause language disorder on Attention Deficit Disorder patient, at case Ichsan. This thesis applied case study descriptive qualitative research in which the data are obtained speech of Attention Defisit Disorder patient are receptive disorder and ekspresive (productive) disorder. The data are collected by observational and conversational method supported by participant observational, interviewing, recording, and note taking techniques. Data analysis method, it was used referential and phonetic articulator method. The results of analysis are presented by formal and informal method. After analyzing the data, it is found that language disorder at case Ichsan, there are three receptive disorder, they are sensoris perception, visual and auditoris. The form ekspresive (productive) disorder is phonetically, vowels and diphthongs do not have any disorders, meanwhile consonants are the most of consisting disorder in form of phone replacement and omission. Furthermore, phones additional and phone irrigularity do not occur in Ichsan speech. Language disorder at case Ichsan is caused by heredity factor, disorder speech articulatory, mental retadration, disorder brain, aphasia, receptive, celebral palsy, deprivasi psychosocial, lonely environment, economy social factor, and the habit of incompletely chewed food.